Solution of Sungkai Leaves (Peromena canescens) as a larvicide against the Aedes aegypti mosquito - Nadila, Nadila; Isnawati, Isnawati; Pahruddin, Muhammad; A., Syarifudin (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
The dengue virus causes Dengue hemorrhagic fever (DHF), an infectious disease that a mosquito vector spreads. In 2021 (ABJ), the larvae-free rate in South Kalimantan is 87.15%; in Banjarbaru City, it is 86%, so it has not yet reached the national standard, which is > 95%. This study aims to reduce mosquito larvae using sungkai leaves, a vegetable larvicide. This plant contains many active substances, such as alkaloids, flavonoids, saponins, steroids, triterpenoids, phenolics, and tannins. This type of research involves the application of the True Experiment Design method. The pThird-instar Aedes aegypti larvae make up the population. We used 600 Aedes aegypti larvae with varying concentrations of 0%, 0.1%, 0.3%, 0.6%, 0.9%, 1.2%, 1.5%, and 1.8% in 1000 mL of water, with a contact time of 24 hours. esults of the Kruskal-Wallis Asymp.Sig test were 0.002<a (0.05). The concentrations that effectively killed larvae were 0.3% and 0.6%. At 24 hours of contact, the LC50 value was 1.941%. The toxid unit value was 51.5. Therefore, we can deduce that the sungkai leaf solution plays a significant role in managing Aedes aegypti larvae. It isWe hope the community will grow plants in the river to combat mosquito larvae. h agencies can interact with the public about how to make larvicides. We hope that future researchers will progress from a solution to an extract.